Assessment of various etiological factors for oral squamous cell carcinoma in non-habit patients- a cross sectional case control study - Mudiyayirakkani Muthusamy; Pratibha Ramani; Paramasivam Arumugam; Parthiban Rudrapathy; Boopathi Kangusamy; Vishnu Priya Veeraraghavan; Selvaraj Jayaraman; Balachander Kannan; Anitha Pandi (BMC Oral Health)
Abstract Background Oral squamous cell carcinoma (OSCC) is one of the most prevalent oral cancers in the world. The major etiological factors are considered to be tobacco and alcohol. However, the etiological factors for non-habit associated oral squamous cell carcinoma (NHOSCC) remains an enigma. So we focused in assessing various etiological factors like genetic factor, microbial factor, dental factor and the biochemical factor of non-habit associated oral squamous cell carcinoma. The aim was to assess Harvey Rat Sarcoma Virus gene (HRAS) mutation, total bacterial count, Herpes Simplex Virus-1 (HSV-1), regressive changes of teeth, total antioxidant capacity and its association with NHOSCC. Materials and methods A total of 564 (n = 564) patients with OSCC were included in the study. Out of 564 patients, 282 patients had NHOSCC and 282 patients had habit associated oral squamous cell carcinoma (HOSCC). The isolated DNA from the tissue was subjected to Sanger’s sequencing analysis for mutation analysis of the HRAS gene. The isolated serum was subjected to HSV-1 ELISA analysis and TAC ELISA analysis. The dental cast used to analyze the presence of sharp teeth/ any other form of regressive changes of teeth. Results Firstly, we found 3 novel pathogenic mutations c.16C > A/p.L6M (missense mutation), c.359 T > C/p.L120P (point mutation), c.382C > T/p.R128W (missense mutation) of HRAS gene in NHOSCC samples by genetic analysis. No significant difference was noted in the total bacterial count between the non-habit associated and habit associated oral squamous cell carcinoma (HOSCC). The binary logistic regression showed patients with HSV1 infection have 2.667 odds (2.667 OR, CI, 1.589- 4.484) of getting NHOSCC and it was found to be statistically significant (p < 0.001).The dental analysis revealed that patients with regressive changes have 4.432 odds (4.432 OR, CI, 2.807- 6.998) of getting NHOSCC and it was found to be statistically significant (p < 0.001). The biochemical analysis revealed patients with lower total antioxidant capacity have 0.671 odds (0.671 OR, CI, 0.621–0.725) of getting NHOSCC and was found to be statistically significant (p < 0.001). Our results suggest that the frequency of HRAS mutation in NHOSCC is high. HSV1, oxidative stress and regressive changes of teeth are associated with NHOSCC. Conclusion Our results suggest that the frequency of HRAS mutation in NHOSCC is high. HSV1, oxidative stress and regressive changes of teeth are associated with NHOSCC.